The impact of sport related stressors on immunity and illness risk in team-sport athletes - Keaney, L. C.; Kilding, A. E.; Merien, F.; Dulson, D. K. (Journal of Science and Medicine in Sport, 2018)
Elite team-sport athletes are frequently exposed to stressors that have the potential to depress immunity and increase infection risk. Therefore, the purpose of this review is to describe how team-sport stressors impact upon immune responses, along with exploring whether alterations in these markers have the potential to predict upper respiratory tract illness symptoms. Design: Narrative review. Methods: Salivary secretory immunoglobulin A (SIgA) and T-cell markers have been shown to predict infection risk in individual endurance athletes. Papers discussing the impact of team-sport stressors on SIgA and T-cells were discussed in the review, studies discussing other aspects of immunity were excluded. Journal articles were sourced from PubMed, Web of science and Scopus. Key search terms included team-sport athletes, stressors, immunity, T-cells, cytokines, SIgA and upper respiratory illness. Results: Most team-sport stressors appear to increase risk for illness. An association between reduced SIgA and increased illness incidence has been demonstrated. Intensive training and competition periods have been shown to reduce SIgA, however, it is less clear how additional stressors including extreme environmental conditions, travel, psychological stress, sleep disturbance and poor nutrition affect immune responses. Conclusions: Monitoring SIgA may provide an assessment of a team-sport athletes risk status for developing upper respiratory tract symptoms, however there is currently not enough evidence to suggest SIgA alone can predict illness. Team-sport stressors challenge immunity and it is possible that the combination of stressors could have a compounding effect on immunodepression and infection risk. Given that illness can disrupt training and performance, further research is required to better elucidate how stressors individually and collectively influence immunity and illness. ABSTRACT FROM AUTHOR